Analisis Dan Optimalisasi Pengendalian Pagu Di Kantor Pos Cabang Pembantu (KCP) PT Pos Indonesia - Sandy Muhammad Kautzar; Dety Mulyanti (Universitas Maritim AMNI Semarang, 2023)
PT. Pos Indonesia is one of the first companies engaged in the field of freight forwarding services in Indonesia. Companies need cash to run their business, pay off obligations and distribute dividends to investors. Therefore, maintaining cash liquidity by establishing an internal control system for cash is the most important concern for the company. The purpose of this study is to determine the supervision and control of the KCP ceiling at PT Pos Indonesia. This study used a qualitative method with primary and secondary data collection. The analysis that the researchers did was to use a Cause-Effect Diagram to map the constraints and causes of excess PAGU in KC/KCU. The results in the study found that there were still several ManKug who did not know that PT. Pos Indonesia implements a cross-subsidy system in which if the profit unit retains its funds, it will have a significant impact on units with a deficit. The conclusion from this research is cause and effect (Fish Bone) that there are 6 factors that influence the advantages of PAGU in KC/KCU namely Method, Human Resources, Internal (material), External (environment), System, and Time factors.